2011
DOI: 10.1007/s10549-011-1922-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a weight loss intervention among rural breast cancer survivors

Abstract: Obese breast cancer survivors have increased risk of recurrence and death compared to their normal weight counterparts. Rural women have significantly higher obesity rates, thus weight control intervention may be a key strategy for prevention of breast cancer recurrence in this population. This one arm treatment study examined the impact of a group-based weight control intervention delivered through conference call technology to obese breast cancer survivors living in remote rural locations. The intervention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 47 publications
8
169
4
Order By: Relevance
“…The QOL outcomes were consistent with those found in the survivors of uterine cancer empowered by exercise and healthy diet (SUCCEED) randomized control trial; whereas, QOL did not change with weightloss outcomes [18,23]. However, several other studies conducting lifestyle interventions in female cancer survivors have reported QOL improvements after a group lifestyle intervention with associated weight-loss [42,43]. More research is needed to identify whether QOL is an indicator for weight-loss in female cancer survivors after a lifestyle intervention.…”
Section: Discussionsupporting
confidence: 75%
“…The QOL outcomes were consistent with those found in the survivors of uterine cancer empowered by exercise and healthy diet (SUCCEED) randomized control trial; whereas, QOL did not change with weightloss outcomes [18,23]. However, several other studies conducting lifestyle interventions in female cancer survivors have reported QOL improvements after a group lifestyle intervention with associated weight-loss [42,43]. More research is needed to identify whether QOL is an indicator for weight-loss in female cancer survivors after a lifestyle intervention.…”
Section: Discussionsupporting
confidence: 75%
“…Efforts to control weight may be a key strategy to reduce mortality from cancer as well as to prevent metabolic syndrome. In breast cancer survivors, significant reductions in fasting serum insulins and leptin as well as significant improvement in quality of life were observed with weight control intervention (Befort et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores are indicative of more severe depression; scores of 5, 10, 15, and 20 correspond to mild, moderate, moderately severe, and severe depression, respectively. The PHQ-9 has been shown to have adequate construct validity and criterion validity [62,63], and has been used in studies with cancer patients and survivors [64,65]. The internal consistency for this sample was good (α = 0.86).…”
Section: Patient Health Questionnaire Assessment Of Depression (Phq-9)mentioning
confidence: 99%